2017
DOI: 10.18632/oncotarget.20003
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 3 pathway restricts Marek’s disease virus infection

Abstract: Marek’s disease virus (MDV) is an α-herpesvirus that causes immune suppression and T lymphoma in chickens. Toll-like receptor 3 (TLR3) is critical for the host immune response against MDV infection. Previously, our team demonstrated that pre-treatment of TLR3 agonist poly (I:C) inhibited Marek’s disease virus infection in chicken embryo fibroblasts (CEFs). However, whether TLR3 inhibits the aggravation of MDV infection is unknown. In the current study, we found that TLR3 activation in MDV-infected CEFs effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In mice, it has been reported that the activation of TLR7 increased production of type 1 IFNs (IFNα) [54]. In chickens, type 1 IFNs produced following TLR3 ligand, dsRNA has been shown to inhibit avian viruses such as avian paramyxovirus, avian influenza virus and Marek’s disease virus [5557]. However, we found that no significant induction of type 1 IFNs production following stimulation of avian macrophages with resiquimod.…”
Section: Discussionmentioning
confidence: 60%
“…In mice, it has been reported that the activation of TLR7 increased production of type 1 IFNs (IFNα) [54]. In chickens, type 1 IFNs produced following TLR3 ligand, dsRNA has been shown to inhibit avian viruses such as avian paramyxovirus, avian influenza virus and Marek’s disease virus [5557]. However, we found that no significant induction of type 1 IFNs production following stimulation of avian macrophages with resiquimod.…”
Section: Discussionmentioning
confidence: 60%
“…This was unexpected based on previous studies using the chicken and GaHV-2 model that reported increased levels of pro-inflammatory mediators, both in vivo [29, 30, 38] and in vitro [32]. These responses probably took place within 24 h post-infection, and it is conceived that antiviral effects are linked to the early synthesis of pro-inflammatory cytokines in CEFs [26, 30]. In vivo studies have shown that as early as 3–4 days post-infection, if not earlier, various innate immune responses are detectable under normal circumstances (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…This is of importance because an efficient response to infection in the early recognition of GaHV-2 has been shown to be crucial to the determination of either a positive or negative outcome [26]. Previous studies demonstrated that herpesviruses triggered innate immune signalling cascades when binding to PRRs, including TLRs, retinoic acid-inducible gene I-like receptors (RLRs), and cytosolic DNA sensors [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, additional signals provided by GaHV-2, like the production of DAMPs, might (in contrast to in poly(I:C)-treated cells) be a reason for the significant expression of TLR3-induced defense mechanisms like the activation of NF-jB signaling. One study revealed that TLR3-mediated anti-viral effects in GaHV-2-infected CEF were associated with production of inflammatory cytokines (Zou et al 2017). Therefore, modulation of NF-jB signaling pathways was expected to represent an important target during GaHV-2 infection.…”
Section: Responses To Infection With Gahv-2mentioning
confidence: 99%